Polymer hydrogels usable for nervous tissue repair - Lesný, P; De Croos, J; Prádný, M; Vacík, J; Michálek, J; Woerly, S; Syková, E (Journal of chemical neuroanatomy, 2002)
The implantation of non-resorbable biocompatible polymer hydrogels into defects in the central nervous system can reduce glial scar formation, bridge the lesion and lead to tissue regeneration within the hydrogel. We implanted hydrogels based on crosslinked poly hydroxyethyl-methacrylate (pHEMA) and poly N-(2-hydroxypropyl)-methacrylamide (pHPMA) into the rat cortex and evaluated the cellular invasion into the hydrogels by means of immunohistochemical methods and tetramethylammonium diffusion measurements. Astrocytes and NF160-positive axons grew similarly into both types of hydrogels. We found no cell types other than astrocytes in the pHEMA hydrogels. In the pHPMA hydrogels, we found a massive ingrowth of connective tissue elements. These changes were accompanied by corresponding changes in the extracellular space volume fraction and tortuosity of the hydrogels.
Keywords: Animals; Polyhydroxyethyl Methacrylate; Methacrylates; Connective Tissue; Rats, Wistar; biokompatibilní materiály; methakryláty; polyhydroxyethylmethakrylát; Esters; Polymers; Hydrogels; Drug Evaluation, Preclinical; pojivová tkáň; pohyb buněk; regenerace nervu; Biocompatible Materials; Nerve Regeneration; preklinické hodnocení léčiv; hydrogely; polymery; krysa rodu Rattus; estery; mozková kůra; Cerebral Cortex; Cell Movement; zvířata; Rats; potkani Wistar